The Ecological Risk Assessment of Ash Toxicity in the Freshwater Crustacean Simocephalus vetulus SchÏ•dler 1858 - Al-Naymi, Noor A. Sh.; Mohammed, Ahmed J.; Nashaat, Muhanned R. (Iraqi Journal of Science, 2019)
The estimating of ash toxicity collected from Durah power plant (DPP) which is located in Baghdad Governorate was done by exposed cladoceran Simocephalus vetulus to different ash concentrations. Thus, the first of its kind study by assessing the toxic effect of these effluents in the selected laboratory individual’s food chain. The acute toxicity test of ash was assessed by LC50 and mortality percentage. LC50 of ash on S. vetulus were 0.14, 0.11 and 0.1 ppt during 24, 48 and 72 hr., respectively. On the other hand, it was shown that increasing the concentrations of ash leads to an increase mortality percentage. It was observed that the maximum mortality percentage (LC100) when exposed to 0.2 and 0.19 ppt at 24 hr. of exposing. On the other hand, the minimum mortality percentages were 0% (LC0) when exposed to 0.1 ppt at 24 hr., this percentage increased to 43% and 56% after 48 and 72 hr., respectively. Also, some obvious changes were observed in the animal behavior, such as slowness at first, then settle on the bottom of the beakers with stopped the antenna and thoracic appendages followed by a weak in a heartbeat. It was shown that the ash concentrations result in inhibiting the survival and increased the mortality percentage, this may be related with the presence of the toxic constituents in ash and change in pH level which was caused a harmful effect.